Metode Penentuan Harga Pokok Produksi Terhadap Pencapaian Laba Percetakan Batako Ro’iy - Murniati, Murniati (Indo Publishing, 2025)
This study aims to analyze the effect of the cost of production determination method on profit achievement at Ro’iy Brick Printing Enterprise in Kendari City. The research employs a descriptive quantitative approach with a case study method, where data were collected through observation, interviews, and documentation. The results show that the company has previously used a simple method in calculating the cost of production, by only adding up raw material costs, direct labor, and some operational expenses, without fully accounting for all factory overhead costs such as equipment depreciation and other indirect expenses. This incomplete cost recording leads to inaccurate calculation of the cost of production, resulting in reported profits that do not reflect the actual financial condition. By applying the full costing method, all production cost components are comprehensively recorded, resulting in more objective and reliable calculations of both cost of production and profit. The findings highlight the importance of using the full costing method as a foundation for profit planning and competitive pricing, especially for MSMEs in the concrete block production sector. This research is expected to provide practical contributions to business actors in cost management and profit improvement